Prevalencia de Hepatitis B en Pacientes con VIH/SIDA atendidos UAMP Hospital de Apoyo Chepén - La Libertad, 2018 - 2020 - Mora Chavarry, Juan Carlos (2023)
HIV/AIDS like Hepatitis B are latent and arduous diseases that must be treated. To do this, the objective was to identify the prevalence of hepatitis B in people with HIV/AIDS who attended the "UAMP" strategy of the Chepén Support Hospital during the 2018-2020 period. The sample population were the medical care histories of 83 patients with HIV/AIDS, all with their diagnosis from the laboratory service of surface antigen and anticore for hepatitis B and who meet the inclusion and exclusion criteria. Results: The prevalence of 24.09% of people with HIV/AIDS was found to have liver infection "hepatitis B"; the most frequently affected people are from 30 to 39 years old, with (40%), followed by the group from 40 to 49 years old, with (25%); men are the most affected with 75%, the frequency of preference was heterosexual with 55%; among men, homosexuals were the most affected by sexual choice at 30%, and bisexuals at 15%. Conclusions: Patients with HIV/AIDS have a high prevalence of hepatitis B, and among the affected groups they attribute to the active population. The male population was the most affected and there was a correlation between gender orientation and manifestations of hepatitis B.